Efektifitas Layanan Konseling Kelompok Dengan Teknik Cinema Education Untuk Meningkatkan Kepercayaan Diri Dalam Berwirausaha di Panti Sosial - Rian Hario; Heru Nurrohman (Suluh: Jurnal Bimbingan dan Konseling, 2018)
This study aims to: (1) To determine the effectiveness of group counselling services with cinema education techniques can increase self-confidence in entrepreneurship of students in adolescent foster care and women's work. The type of research used is Experimental Research to look for influences on specific treatments. The sample in this study were adolescent social care institutions for adolescents and 2016/2017 women's works which amounted to 8 students, consisting of 8 male students. Data collection techniques used are scale and observation. Data analysis using hypothesis testing paired sample t-test to calculate the comparison of the results of the average pretest and posttest of students. Based on the results of the hypothesis it is known the value of sig. (2-tailed) Which is 0.002 <0.05, which means that there is a significant difference between pretest and posttest. The pretest results showed that the average scale of students' suspensions was 81.13, which was included in the category of moderate social prejudice and for the suspension of posttest scores of students, 91.75 was involved in the high class. From these data shows that there is an increase in self-confidence in entrepreneurship of students after the group counselling services with cinema education techniques are implemented